Research on the development and utilization mode of mine water resources. (November 2019) - Zhang, Nan; He, Hongmou; Guo, Xinwei; Li, Shu; Ni, Shenhai; Peng, Yuejin
Abstract: China's mine water comprehensive utilization rate is low. The main reason for the increase in the utilization rate after 2015 is the reduction in coal production. The shutdown of a large number of coal mines by capacity has objectively led to a reduction in mine water volume. Based on the development and utilization of mine water, this paper clarifies the characteristics of mine water utilization mode, and discusses the classification of mine water utilization mode and suggestions for safeguard measures in terms of mine water utilization targets and treatment difficult. The research undertook in this paper will expand the utilization of mine water and improve the utilization rate of mine water. It will help enterprises realize the transformation of mine water into waste and realize the value-added effect of mine water. It is desirable for the unconventional water resources will be integrated into the water source. It can help ease the contradiction between water supply and demand in water shortage areas and improve the efficiency and utilization efficiency of regional water resources allocation.